The effects of providing peer feedback on learners’ genre awareness in English as a foreign language business letter writing - Wu, Huizhen; Zhu, Huimin; Yang, Xiaohu (Frontiers in Psychology, 2022)
Despite the importance of the genre awareness in facilitating the effective communication in the global business context and the need to teach and practice writing for various social purposes, there’s scant classroom-based research on effects of providing peer feedback on EFL learners’ genre awareness in business writing for fulfilling the particular communicative purpose. This quasi-experimental study examined whether providing peer feedback to students’ writings at varying levels exerted different effects on improving feedback providers’ genre awareness in business letter writing. Sixty business English majors, taking the business writing course for one year under the tutelage of the same instructor, participated in the study. They were randomly assigned to the Experimental Group who reviewed the students’ drafts at different levels (high, medium and low) and gave written comments and the control group who received no treatment but did self-revision. Both groups followed the genre-specific evaluation criteria during peer feedback and self-revision. Our results showed that the students in the experimental group had better performance and maintenance than the control group at the immediate posttest, the transfer posttest as well as the delayed transfer posttest. Moreover, providing weaknesses comments on both the low-quality and the medium-quality drafts had significant associations with their own writing quality at the subsequent tests while providing merits feedback on the high-quality drafts had statistically significant correlations with their own writing quality at the immediate posttest and the delayed transfer posttest. Further stepwise regression analyses demonstrated that only offering weakness comments to the medium-quality drafts significantly predicted the reviewers’ overall writing quality in the immediate posttest, the transfer posttest and the delayed transfer posttest. Tentative research and pedagogical implications of the findings were discussed.